18th IEEE International Conference on Software Quality, Reliability, and Security (QRS 2018) and 4th International Symposium on System and Software Reliability (ISSSR 2018) (IEEE transactions on reliability, 2018)
Describes the above-named upcoming conference event. May include topics to be covered or calls for papers.